Knowledge Mapping of Enterprise Network Research in China: A Visual Analysis Using CiteSpace - Yang, Wancheng; Wang, Shaofeng; Chen, Chen; Leung, Ho Hon; Zeng, Qi; Su, Xin (Frontiers in Psychology, 2022)
Enterprise Network (EN) has increasingly gained popularity in academia. Over the past few decades, a substantial amount of EN studies have been published in China. Drawing upon a sample of 603 papers retrieved from CSSCI database between 1998 and 2020, this study aims to delve into the status quo, knowledge base, research focus, and evolutionary trends of EN research in China. A multifaceted bibliometric analysis was performed using CiteSpace. First, the current status of Chinese EN research was depicted by statistically visualizing the volume of publications, key journals, key authors and key institutions of sample articles. Second, a cocitation analysis oriented towards authors, sources, and studies extensively cited by sample papers was conducted to reveal the knowledge base of EN research in China. Third, the frontier hotspots of Chinese EN research were uncovered by progressively performing a coword analysis, a cooccurrence analysis and a cluster analysis. Finally, a temporal analysis was carried out on the basis of the extracted high-frequency keywords of sample literature to summarize the development trends of EN research in China. The findings mainly indicate that EN in China tends to localize whilst taking inspirations from western theories and integrating them with domestic settings. The research output of domestic researchers such as Luo Jiade, Bian Weijie, and Wei Jiang, alongside with western scholars such as Granovetter, Burt, and Gulati has co-formed the knowledge base of EN in China. Research topics including conceptualization of EN, EN as indicators of enterprise development, EN's impact on start-ups, mechanisms of EN's effect; and governance of EN have been the main building blocks of Chinese EN studies. A potential direction for future research has been identified as the integration between EN and other forms of networks such as geographical network, urban network, and knowledge network. The findings offer conceptual support and practical guidelines for EN researchers to determine potential directions and seek academic collaborations in the future.